The function and clinical implication of YTHDF1 in the human system development and cancer - Wenjun Ren; Yixiao Yuan; Yongwu Li; Luciano Mutti; Jun Peng; Xiulin Jiang (BMC, 2023)
Abstract YTHDF1 is a well-characterized m6A reader protein that is essential for protein translation, stem cell self-renewal, and embryonic development. YTHDF1 regulates target gene expression by diverse molecular mechanisms, such as promoting protein translation or modulating the stability of mRNA. The cellular levels of YTHDF1 are precisely regulated by a complicated transcriptional, post-transcriptional, and post-translational network. Very solid evidence supports the pivotal role of YTHDF1 in embryonic development and human cancer progression. In this review, we discuss how YTHDF1 influences both the physiological and pathological biology of the central nervous, reproductive and immune systems. Therefore we focus on some relevant aspects of the regulatory role played by YTHDF1 as gene expression, complex cell networking: stem cell self-renewal, embryonic development, and human cancers progression. We propose that YTHDF1 is a promising future cancer biomarker for detection, progression, and prognosis. Targeting YTHDF1 holds therapeutic potential, as the overexpression of YTHDF1 is associated with tumor resistance to chemotherapy and immunotherapy.